Developing Factors Capacity Building: For the Tourism Industry - Shahparan, Mohammad; Odilov , Akmaljon (Adpebi International Journal of Multidisciplinary Sciences, 2024)
Developing capacity building for the tourism industry is important to grow the capacity of community-based tourism factors. Among all the famous tourist destinations community-based tourism is counted as the alternative tourist destination, which is formed by the capacity building factors. This paper aims to identify the key elements and factors for capacity building for the tourism industry and explore some variables that enhance capacity building for tourism. Qualitative methods are applied in this study. Data was collected from different streamlined journals, research papers, and books related to capacity building for tourism sectors. In the future, this paper can help to apply the theoretical concept to develop the capacity of the tourism industry.